Damage Characteristics of Argillaceous Quartz Sandstone Mesostructure under Different Wetting-drying Conditions - Deng, Lixu; Yang, Jianfei; Zhang, Guodong; Zhang, Yaxin; Chen, Guangfu; Li, Xijun (Periodica Polytechnica Civil Engineering, 2022)
Extensive water–rock interaction in the Three Gorges Reservoir area of the Yangtze River leads to rock mass deterioration along the reservoir banks. However, mineral evolution behavior and its effect on the mesostructure deterioration of rocks under the wetting–drying cycle condition remain unknown. So, the wetting–drying cycle tests were conducted on peculiar argillaceous quartz sandstone in TGRA under neutral (pH = 7) and alkaline (pH = 10) water environments. Here, we provided detailed physical and microscopy images data to determine the control mechanism of mineral behavior on the evolution of sandstone’s mesostructure. Under the neutral condition, repeated “absorption and swelling–dehydration and contraction” of clay minerals leads to the repeated physical action of “squeezing–unloading” in the interior of a rock. This results in the initiation and gradual expansion of cracks in the framework mineral quartz, exhibiting failure mode from the interior to the exterior. In contrast, under the alkaline condition, the dissolution on the surface of quartz particles leads to the expansion and connection of pores, implying that the sandstone exhibits failure mode from the exterior to the interior. Moreover, the internal mechanical analysis indicates the minerals are at high pressure because of the expansion of clay minerals in the neutral solution. However, in an alkaline water environment, the extrusion pressure of framework mineral quartz decreases significantly and is not easily broken due to increased porosity. Thus, the evolution behavior of minerals in different water environments plays an important role in the damage of the rock.